(untitled) (Research, Society and Development, 2022)
Capecitabine is a chemotherapy drug widely used in the treatment of metastatic breast cancer. Despite the clinical benefits, adverse events can influence the continuity of therapy. The on/off protocol was designed with the intention of optimizing treatment with capecitabine due to a likely reduction in adverse events. Thus, the aim of the study was to describe the incidence of adverse events during the use of standard and on/off capecitabine protocols. A retrospective cohort study was carried out, in which 221 patients with metastatic breast cancer were analyzed. The sample was divided into groups and subgroups: A - standard; B - on/off; A1 and B1 reduced dose; A2 and B2 full dose. The adverse event with the highest overall incidence (84%) was palmar-plantar erythrodysesthesia syndrome. Most adverse events showed no statistically significant variation in incidence between groups A and B. A higher incidence of adverse events was observed in patients who underwent full dose in both protocols. Regarding severity, most were classified as grade 1 and there was no statistical difference between groups A and B. The study suggests that switching from standard protocol to on/off, with the aim of reducing the incidence and severity of adverse events, does not have a significant impact. Dose reduction is a viable alternative to decrease the incidence of adverse reactions and is clinically relevant in some cases.